Cryotherapy Intervention to Reduce Cannulation Pain in Hemodialysis Patients - Giri Susanto; Wati Jumaiyah; Siti Latipah; Fitrian Rayasari (Indonesian Journal of Global Health Research, 2025)
End-stage chronic kidney disease requires hemodialysis with vascular access via an arteriovenous fistula (AVF). AVF cannulation is often painful. Cryotherapy, a cold therapy that can reduce pain through gate control theory, is used. Objective to assess the effectiveness of cryotherapy in reducing pain during arteriovenous fistula (AVF) puncture in hemodialysis patients. This study applied an Evidence-Based Nursing Practice approach, including a literature search through PubMed and ProQuest databases. The primary reference used was a systematic review and meta-analysis entitled "The Effect of Cryotherapy on Pain Associated with Arteriovenous Fistula Puncture in Hemodialysis Patients." This study used a single-group pre-test and post-test design. The population consisted of hemodialysis patients with AVFs who met the inclusion criteria, patients undergoing regular hemodialysis, using AVF access, and who had been using AVF access for more than three months. Exclusion criteria included patients who had taken pain medication within three hours before hemodialysis. A total of 19 participants were included. The intervention involved applying ice gel compresses to the cannulation area for 10 minutes before the procedure. Pain levels were measured using a Visual Analogue Scale before and after the intervention. Data were analyzed using paired t-tests and Chi-square tests. Cryotherapy significantly reduced AVF cannulation pain, with a p-value of 0.001. There was a difference in pain levels before and after the cryotherapy intervention.